Lithium ion battery current collector surface treatment method, current collector and lithium ion battery
By coating the current collector of the lithium-ion battery with phytic acid assisted phosphorus-doped graphene, the problem of insufficient bonding strength between the current collector and the electrode material is solved, and the electrode stability and service life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411775080.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The bonding strength between the current collector and the electrode material of the lithium-ion battery is insufficient, which affects the ohmic impedance, electrode stability and cycle life of the battery.
Phosphorus-doped graphene was synthesized by electrochemical methods and coated onto the positive and negative current collector of the lithium-ion battery, and the binding of the current collector and the active substance was enhanced by the hexagonal structure of phytic acid.
The electrode stability and service life of lithium-ion batteries are significantly improved, and the bonding strength between the current collector and the electrode material is enhanced.
Smart Images

Figure CN119812345A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and more specifically, relates to a surface treatment method for a lithium ion battery current collector, a current collector and a lithium ion battery. Background Art
[0002] In the production and preparation of lithium-ion batteries, aluminum foil and copper foil are used as current collectors for battery electrodes. However, the surfaces of metal foils such as aluminum foil and copper foil are too flat and smooth. When they come into contact with granular active materials, the contact area is small and the bonding strength is weak, which affects the battery's ohmic impedance, electrode stability, cycle life and other indicators.
[0003] Surface pretreatment of the current collector and coating with specific materials can effectively solve this problem. Carbon materials have a special porous structure and a large contact area when in contact with granular active substances. Therefore, carbon materials are widely used in the surface treatment of lithium-ion battery current collectors, such as graphene. However, although the introduction of graphene can increase the contact area between the current collector and the active substance, the bonding strength between graphene and the active substance is still not guaranteed, and the resulting electrode peeling strength is often low.
[0004] The surface of phosphorus-doped graphene generated with the assistance of phytic acid is bonded with abundant phytic acid molecules. Phytic acid itself has a special hexagonal structure. Its six "tentacles" can achieve close contact between the current collector and the active material, solving the above problems. Summary of the invention
[0005] In view of the above technical defects of the prior art, the present invention provides a surface treatment method for a lithium ion battery current collector, a current collector and a lithium ion battery, which can enhance the bonding strength between the current collector and the electrode material.
[0006] To achieve the above object, the present invention provides a lithium ion battery current collector surface treatment method as follows:
[0007] 1) using phytic acid solution and carbon paper as raw materials, synthesizing phosphorus-doped graphene by an electrochemical method; the mass ratio of phytic acid to carbon paper is 50:1 to 100:1, and too low a phytic acid dosage will affect the performance of the synthesized phosphorus-doped graphene;
[0008] 2) Coating phosphorus-doped graphene onto the positive and negative current collectors of lithium-ion batteries.
[0009] Preferably, the electrochemical method in step 1) is an electrochemical solution stripping method;
[0010] The electrochemical solution stripping method uses a DC constant voltage source as a stripping power source; the electrochemical solution stripping method uses a phytic acid solution as a stripping solution and carbon paper as an electrochemical stripping carbon source;
[0011] The chemical formula of phytic acid is C6H 18 O 24 P6, the electrochemical solution stripping method uses carbon paper as a carbon source, and the chemical formula is C.
[0012] Preferably, the voltage of the DC constant voltage source is 5 to 12V, for example, it can be 5V, 6V, 7V, 8V, 9V or 12V, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; a DC constant voltage source voltage that is too high will lead to oxidation of the synthesized graphene material, and a DC constant voltage source voltage that is too low will lead to incomplete electrochemical stripping of the carbon paper; a DC constant voltage source action time that is too short will lead to incomplete electrochemical stripping of the carbon paper.
[0013] The action time of the DC constant voltage source is 0.2 to 1 h, for example, it can be 0.2 h, 0.4 h, 0.6 h, 0.8 h or 1 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] Preferably, the molar concentration of the phytic acid solution is 2 to 8 mol / L, for example, 2 mol / L, 4 mol / L, 6 mol / L or 8 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; too high a concentration of the phytic acid solution will affect the structural strength of the carbon paper and cause incomplete electrochemical stripping, while too low a concentration of the phytic acid solution will affect the doping rate of the generated graphene material; too high a thickness of the carbon paper will affect the electrochemical stripping reaction, while too low a concentration will affect the concentration of the product.
[0015] The thickness of the carbon paper is 0.1-1 mm, for example, 0.1 mm, 0.3 mm, 0.5 mm, 0.7 mm, 0.9 mm or 1 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] Preferably, the positive electrode current collector material is aluminum foil and the negative electrode current collector material is copper foil.
[0017] Preferably, in step 2), the method of coating the phosphorus-doped graphene on the surface of the positive and negative electrode current collectors is a flat plate coating method or a brush coating method.
[0018] Preferably, the thickness of the phosphorus-doped graphene coated on the surface of the positive and negative electrode current collector is 50 to 500 nm, for example, 50 nm, 100 nm, 200 nm, 300 nm or 500 nm, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. Too high coating thickness affects the battery energy density, and too low coating thickness has limited effect on the modification of the current collector surface.
[0019] The surface of the phosphorus-doped graphene synthesized by the present invention is bonded with abundant phytic acid molecules. Phytic acid has a special hexagonal structure, and its six "tentacles" link the current collector and the electrode material together, which can effectively improve the electrode stability and service life of the lithium-ion battery.
[0020] The second invention provides a current collector obtained by the above-mentioned surface treatment method, wherein the surface of the current collector is coated with phosphorus-doped graphene.
[0021] In a third aspect, the present invention provides a lithium ion battery, wherein the surface of the electrode material of the lithium ion battery is the above-mentioned current collector, and the phosphorus-doped graphene on the surface of the current collector is located between the electrode material and the current collector.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In the present invention, the phosphorus-doped graphene surface on the lithium-ion battery current collector is bonded with abundant phytic acid molecules. Phytic acid has a special hexagonal structure, and its six "tentacles" link the current collector and the active material together, which can effectively improve the electrode stability and service life of the lithium-ion battery.
[0024] The invention discloses a method for treating the surface of a lithium-ion battery current collector by using phosphorus-doped graphene generated with the aid of phytic acid, and the purpose of the method is to use phosphorus-doped graphene generated with the aid of phytic acid to perform surface coating treatment of a specific thickness on the aluminum foil and copper foil current collector of the lithium-ion battery, so as to enhance the bonding strength between the current collector and the active material. The method can effectively improve the stability and service life of the lithium-ion battery electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 a is a schematic diagram of phosphorus-doped graphene generated with the assistance of phytic acid in the method of the present invention, Figure 1 b is a schematic diagram of the molecular structure of phytic acid;
[0026] Figure 2 This is an X-ray photoelectron spectrum of phosphorus-doped graphene generated with the assistance of phytic acid in Example 1 of the present invention;
[0027] Figure 3 Schematic diagram of the mechanism of action of phosphorus-doped graphene assisted by phytic acid on the surface of lithium-ion battery current collector in the method of the present invention;
[0028] Figure 4 This is a scanning electron microscope image of the phosphorus-doped graphene generated with the assistance of phytic acid in Example 1 of the present invention after being coated on the current collector of a lithium-ion battery.
[0029] In all drawings, the same reference numerals are used to denote the same structures or parts, wherein: 1 - graphene, 2 - phytic acid, 3 - current collector, 4 - electrode material, lithium ion battery 5. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The present invention provides a method for treating the surface of a lithium ion battery current collector by using phytic acid-assisted phosphorus-doped graphene, comprising the following steps:
[0032] 1) Phytic acid solution and carbon paper are used as raw materials (the mass ratio of phytic acid to carbon paper is 50:1-100:1), and phosphorus-doped graphene is synthesized by an electrochemical solution stripping method. The electrochemical solution stripping method uses a direct current constant voltage source as a stripping power source, a phytic acid solution as a stripping solution, and carbon paper as an electrochemical stripping carbon source; the direct current constant voltage source voltage is 5-12V, and the direct current constant voltage source action time is 0.2-1h; the phytic acid solution concentration is 2-8mol / L, and the carbon paper thickness is 0.1-1mm.
[0033] 2) The phosphorus-doped graphene generated with the assistance of phytic acid is coated on the positive and negative current collectors (aluminum foil and copper foil) of the lithium-ion battery. The surface of the phosphorus-doped graphene is bonded with abundant phytic acid molecules. Phytic acid has a special hexagonal structure, and its six "tentacles" link the current collector and the active material together, which can effectively improve the electrode stability and service life of the lithium-ion battery. The method of coating the phosphorus-doped graphene on the surface of the current collector is a flat coating method or a brush coating method, and the thickness of the phosphorus-doped graphene coated on the surface of the current collector is 50 to 500 nm.
[0034] Figure 1 a is a schematic diagram of phosphorus-doped graphene generated with the assistance of phytic acid in the method of the present invention. As can be seen from the figure, the surface of graphene 1 of phosphorus-doped graphene generated with the assistance of phytic acid is connected to abundant phytic acid 2. Figure 1 b is a schematic diagram of the molecular structure of phytic acid 2. As can be seen from the figure, phytic acid 2 has a special hexagonal structure. These six "tentacles" can connect to graphene 1 on one side and to the target substance on the other side. Figure 3 It is a schematic diagram of the mechanism of action of phosphorus-doped graphene assisted by phytic acid on the surface of lithium-ion battery current collector 3 in the method of the present invention. As can be seen from the figure, the hexagonal phytic acid 2 realizes the connection between the graphene 1 and the electrode material 4 on the lithium-ion battery current collector 3, and strengthens the bonding strength between the current collector 3 and the electrode material 4.
[0035] In order to explain the method of the present invention in more detail, the following is described in conjunction with embodiments:
[0036] Example 1
[0037] 1) Phytic acid 2 solution and carbon paper were used as raw materials (the mass ratio of phytic acid to carbon paper was 50:1), and phosphorus-doped graphene was synthesized by electrochemical solution stripping method. The electrochemical solution stripping method used a DC constant voltage source as the stripping power source, and phytic acid 2 solution was used as the stripping solution. The DC constant voltage source voltage was 5V, the DC constant voltage source action time was 0.5h, the phytic acid 2 solution concentration was 5mol / L, and the carbon paper thickness was 0.5mm. Figure 1 As shown, the surface of graphene 1 of the generated phosphorus-doped graphene is bonded with abundant phytic acid 2 molecules with a special hexagonal structure.
[0038] Figure 2 The X-ray photoelectron spectrum of phosphorus-doped graphene obtained in Example 1 is shown. Figure 2 It can be seen that the generated graphene 1 has an obvious P2p peak in the X-ray photoelectron spectrum, which indicates that the phosphorus element is successfully doped into the graphene 1, further proving that the phytic acid 2 molecule is successfully connected to the surface of graphene 1.
[0039] 2) The phosphorus-doped graphene generated with the aid of phytic acid is coated on the positive and negative current collectors of the lithium-ion battery with a coating thickness of 200 nm. Figure 3 As shown, the six “tentacles” of phytic acid 2 link the current collector 3 and the electrode material 4 together.
[0040] Figure 4 Shown is a scanning electron microscope image of the phosphorus-doped graphene generated with the assistance of phytic acid in Example 1 after being coated on the lithium-ion battery current collector 3.
[0041] 3) Lithium iron phosphate was used as the active material and lithium sheet was used as the counter electrode to assemble a lithium ion battery 5. The capacity retention rate of the battery was tested at a current density of 200 mA / g for 300 cycles.
[0042] Example 2
[0043] The method is the same as Example 1 except that the voltage of the electrochemical stripping DC constant voltage source in step 1) is 8V.
[0044] Example 3
[0045] The method is the same as Example 1 except that the voltage of the electrochemical stripping DC constant voltage source in step 1) is 12V.
[0046] Example 4
[0047] 1) Phytic acid 2 solution and carbon paper were used as raw materials (the mass ratio of phytic acid to carbon paper was 70:1), and phosphorus-doped graphene was synthesized by electrochemical solution stripping method. The electrochemical solution stripping method used a DC constant voltage source as the stripping power source, and phytic acid 2 solution was used as the stripping solution. The DC constant voltage source voltage was 5V, the DC constant voltage source action time was 0.2h, the phytic acid 2 solution concentration was 2mol / L, and the carbon paper thickness was 0.1mm. Figure 1 As shown, the surface of graphene 1 of the generated phosphorus-doped graphene is bonded with abundant phytic acid 2 molecules with a special hexagonal structure.
[0048] 2) The phosphorus-doped graphene generated with the aid of phytic acid is coated on the positive and negative current collectors of the lithium-ion battery with a coating thickness of 50 nm. Figure 3 As shown, the six “tentacles” of phytic acid 2 link the current collector 3 and the electrode material 4 together.
[0049] 3) Lithium iron phosphate was used as the active material and lithium sheet was used as the counter electrode to assemble a lithium ion battery 5. The capacity retention rate of the battery was tested at a current density of 200 mA / g for 300 cycles.
[0050] Example 5
[0051] The method is the same as Example 4 except that the action time of the electrochemical stripping DC constant voltage source in step 1) is 0.5 h.
[0052] Example 6
[0053] The method is the same as Example 4 except that the electrochemical stripping DC constant voltage source action time in step 1) is 1 hour.
[0054] Example 7
[0055] 1) Phytic acid 2 solution and carbon paper were used as raw materials (the mass ratio of phytic acid to carbon paper was 60:1), and phosphorus-doped graphene was synthesized by electrochemical solution stripping method. The electrochemical solution stripping method used a DC constant voltage source as the stripping power source, and phytic acid 2 solution was used as the stripping solution. The DC constant voltage source voltage was 10V, the DC constant voltage source action time was 1h, the phytic acid 2 solution concentration was 2mol / L, and the carbon paper thickness was 0.5mm. Figure 1 As shown, the surface of graphene 1 of the generated phosphorus-doped graphene is bonded with abundant phytic acid 2 molecules with a special hexagonal structure.
[0056] 2) The phosphorus-doped graphene generated with the aid of phytic acid is coated on the positive and negative current collectors of the lithium-ion battery with a coating thickness of 200 nm. Figure 3 As shown, the six “tentacles” of phytic acid 2 link the current collector 3 and the electrode material 4 together.
[0057] 3) Lithium iron phosphate was used as the active material and lithium sheet was used as the counter electrode to assemble a lithium ion battery 5. The capacity retention rate of the battery was tested at a current density of 200 mA / g for 300 cycles.
[0058] Example 8
[0059] The method is the same as Example 7 except that the concentration of the phytic acid solution in step 1) is 5 mol / L.
[0060] Example 9
[0061] The method is the same as Example 7 except that the concentration of the phytic acid solution in step 1) is 8 mol / L.
[0062] Example 10
[0063] 1) Phytic acid 2 solution and carbon paper were used as raw materials (the mass ratio of phytic acid to carbon paper was 100:1), and phosphorus-doped graphene was synthesized by electrochemical solution stripping method. The electrochemical solution stripping method used a DC constant voltage source as the stripping power source, and phytic acid 2 solution was used as the stripping solution. The DC constant voltage source voltage was 8V, the DC constant voltage source action time was 0.5h, the phytic acid 2 solution concentration was 5mol / L, and the carbon paper thickness was 0.5mm. Figure 1 As shown, the surface of graphene 1 of the generated phosphorus-doped graphene is bonded with abundant phytic acid 2 molecules with a special hexagonal structure.
[0064] (2) The phosphorus-doped graphene generated with the aid of phytic acid is coated on the positive and negative current collectors of the lithium-ion battery with a coating thickness of 50 nm. Figure 3 As shown, the six “tentacles” of phytic acid 2 link the current collector 3 and the electrode material 4 together.
[0065] 3) Lithium iron phosphate was used as the active material and lithium sheet was used as the counter electrode to assemble a lithium ion battery 5. The capacity retention rate of the battery was tested at a current density of 200 mA / g for 300 cycles.
[0066] Embodiment 11
[0067] The method is the same as Example 10 except that the coating thickness of the phosphorus-doped graphene in step 2) is 200 nm.
[0068] Example 12
[0069] The method is the same as Example 10 except that the coating thickness of the phosphorus-doped graphene in step 2) is 500 nm.
[0070] Embodiment 13
[0071] The method is the same as Example 1 except that the active material in step 3) is a 523 series ternary material.
[0072] Embodiment 14
[0073] The method is the same as Example 1 except that the active material in step 3) is graphite material.
[0074] Comparative Example 1
[0075] The method is the same as that of Example 1 except that the surface treatment of the current collector is not performed.
[0076] Comparative Example 2
[0077] The method is the same as Example 13 except that the surface treatment of the current collector is not performed.
[0078] Comparative Example 3
[0079] The method is the same as Example 14 except that the surface treatment of the current collector is not performed.
[0080] The test results are shown in Table 1:
[0081] Table 1
[0082] Example / Comparative Example 300 cycles capacity retention rate / % Example 1 86 Example 2 86 Example 3 87 Example 4 83 Example 5 85 Example 6 85 Example 7 79 Example 8 87 Example 9 89 Example 10 88 Embodiment 11 89 Example 12 82 Embodiment 13 80 Embodiment 14 72 Comparative Example 1 53 Comparative Example 2 49 Comparative Example 3 38
[0083] From Table 1, we can see the following points:
[0084] (1) It can be seen from Examples 1 to 3 that the change of the electrochemical stripping DC constant voltage source voltage within the range of 5V to 12V in step (1) of the method has little effect on the cycle performance of the lithium-ion battery.
[0085] (2) It can be seen from Examples 4 to 6 that the change in the electrochemical stripping DC constant voltage source action time within 0.2 h to 1 h in step (1) of the method has little effect on the cycle performance of the lithium-ion battery.
[0086] (3) It can be seen from Examples 7 to 9 that the concentration of the phytic acid solution in step (1) of the method has a significant effect on the cycling performance of the lithium-ion battery. When the concentration is 2 mol / L, the capacity retention rate of the lithium-ion battery after cycling is significantly lower than that of the concentrations of 5 mol / L and 8 mol / L.
[0087] (4) It can be seen from Examples 10 to 12 that the coating thickness of phosphorus-doped graphene in step (2) of the method has a significant effect on the cycling performance of the lithium-ion battery. When the thickness is 500 nm, the capacity retention rate of the lithium-ion battery after cycling is significantly lower than the results with thicknesses of 50 nm and 200 nm.
[0088] (5) It can be seen from Example 1 and Comparative Example 1, Example 13 and Comparative Example 2, and Example 14 and Comparative Example 3 that the cycle performance of lithium batteries assembled with current collectors coated with phosphorus-doped graphene is significantly improved regardless of whether it is lithium iron phosphate, ternary or graphite material.
[0089] In summary, in the method of the present invention, the surface of the phosphorus-doped graphene on the lithium-ion battery current collector is bonded with abundant phytic acid molecules. Phytic acid has a special hexagonal structure, and its six "tentacles" link the current collector and the active material together, which can effectively improve the electrode stability and service life of the lithium-ion battery for electromagnetic emission.
[0090] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for treating the surface of a lithium ion battery current collector, characterized in that: The surface treatment method is as follows: 1) using phytic acid solution and carbon paper as raw materials, synthesizing phosphorus-doped graphene by an electrochemical method; the mass ratio of the phytic acid to the carbon paper is 50:1 to 100:1; 2) Coating phosphorus-doped graphene onto the positive and negative current collectors of lithium-ion batteries.
2. The method for treating the surface of a lithium ion battery current collector according to claim 1, characterized in that: The electrochemical method in step 1) is an electrochemical solution stripping method.
3. The method for treating the surface of a lithium ion battery current collector according to claim 2, characterized in that: The electrochemical solution stripping method uses a direct current constant voltage source as a stripping power source; the electrochemical solution stripping method uses a phytic acid solution as a stripping solution and carbon paper as an electrochemical stripping carbon source.
4. The method for treating the surface of a lithium ion battery current collector according to claim 3, characterized in that: The voltage of the DC constant voltage source is 5 to 12V; the action time of the DC constant voltage source is 0.2h to 1h.
5. The method for treating the surface of a lithium ion battery current collector according to claim 3, characterized in that: The molar concentration of the phytic acid solution is 2-8 mol / L; the thickness of the carbon paper is 0.1-1 mm.
6. The method for treating the surface of a lithium ion battery current collector according to claim 1, characterized in that: In the step 2), the positive electrode current collector material is aluminum foil, and the negative electrode current collector material is copper foil.
7. The method for treating the surface of a lithium ion battery current collector according to claim 1, characterized in that: In the step 2), the method of coating the phosphorus-doped graphene on the surface of the positive and negative electrode current collectors is a flat plate coating method or a brush coating method.
8. The method for treating the surface of a lithium ion battery current collector according to any one of claims 1 to 7, characterized in that: The thickness of the phosphorus-doped graphene coated on the surface of the positive and negative electrode current collectors is 50 to 500 nm.
9. A current collector obtained by the surface treatment method according to any one of claims 1 to 8, wherein the surface of the current collector is coated with phosphorus-doped graphene.
10. A lithium ion battery, characterized in that: The surface of the electrode material of the lithium-ion battery is the current collector according to claim 9, and the phosphorus-doped graphene on the surface of the current collector is located between the electrode material and the current collector.
Citation Information
Patent Citations
Functionalized porous graphene and preparation method thereof
CN109678142A
Low-temperature electrode plate, preparation method thereof and low-temperature lithium battery
CN111816882A
Surface modification treatment method for lithium slurry battery current collector
CN112599780A